Maternal healthcare as an international human right: the influence of culture and religion on access to maternal healthcare in Southern African states of Botswana, South Africa and Zimbabwe - Mngomezulu, Khumo Nokuthula (My University, 2023)
Although globally, there has been a significant decline of maternal mortality, as evidenced by 44% decline in maternal mortality recorded between 1990 to 2015, the maternal mortality is still unacceptably high. Globally, there has been a growing concern about the unacceptably high maternal mortality, and it is estimated that in 2017 approximately 810 women died every day from pregnancy- or childbirth-related complications around the world.(WHO, 2017). Moreover, it has been observed that the countries that suffer most are the ones in less developed economies. Therefore, the aim of the study was to critically assess the implementation and internalisation of international norms related to maternal health with a view to recommend strategies that might address the current challenges being faced in the provision and uptake of maternal healthcare in the Southern African region. The study population was drawn from three case studies, that is, Botswana, South Africa and Zimbabwe. The target population comprised health care workers, traditional healers, religious leaders, spiritual healers and senior health care officers and government officials. Data for the study was collected through interviews and documents review. The study made use of the norm cascade model to critically evaluate the level of internalisation of the international norms related to maternal health. Findings from the study revealed that despite the existence of international norms related to maternal health, internalisation of those norms were a challenge in those three countries, due to a number of factors. Some of the factors were identified as socio-cultural factors, religious ideological factors, economic factors and education levels. Another finding showed that the medicalisation of maternal related issues has been proven to be less effective , especially in the context of African people who find themselves in the middle of other factors that the entrepreneurs of the international norms were not familiar with due to diversity of background and experience. The research design used in the study is a comparative case study design that encompasses qualitative semi-structured in-depth interviews, focus group discussion, document and thematic analysis. Persons interviewed in the depth interviews included, medical doctors, midwives, traditional healers, religious leaders and experts on culture. The study recommends an all-inclusive approach to maternal related issues, thus Southern African governments should integrate both allopathic approach and traditional / cultural approach in order to get a buy in into the norms and internalisation.
A thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: Maternal mobility; Maternal morbidity; International norms